Enhancing Learners’ Spelling Skills with an Interactive Chatbot Facilitator - Al Ghaithi, Ali; Behforouz, Behnam; Isyaku, Hassan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study attempted to design an interactive chatbot to function as the facilitator for improving spelling skills and elicit students’ perceptions of using chatbots in the language learning process. To collect the required data, 60 Omani EFL students were divided equally into control and experimental groups, each with 30 students, to collect the necessary data. Three instruments were used to collect the necessary data, including a newly researcher-designed WhatsApp bot, a perceptions questionnaire adopted from Khan et al. [1], and the NorthStar GCC book series to elicit the vocabulary for spelling practice. The findings disclosed that using interactive chatbots in a learning context improved spelling skills among experimental group participants. Learners who interacted with the bot during the treatment period showed favorable perceptions toward its use in learning. Teachers would benefit from using a WhatsApp bot to send extra materials, allowing students to access materials without time and place limitations.